2017
DOI: 10.18632/oncotarget.16582
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptors and androgen receptor and their clinical significance in gastric cancer

Abstract: Despite the mounting studies exploring the role of estrogen receptor alpha (ERα), estrogen receptor beta (ERβ) and androgen receptor (AR) in gastric cancer (GC), there remain controversies in those findings. The present study investigated the expression of ERα, ERβ and AR in Chinese gastric cancer by immunohistochemistry, analyzed their clinical relevance in gastric cancer, and examined the potential mechanisms by which ERα and AR modulated GC progression. The positive rate of ERα, ERβ and AR in GC tissues was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
4
44
0
7
Order By: Relevance
“…Increased serum phytoestrogen concentrations have also been shown to be inversely correlated to risk of gastric cancer in a study of male and female Korean individuals [78]. Furthermore, Chinese ERα positive gastric cancer patients, had a significantly worse prognosis compared to those that were ERβ positive [79]. The most well characterized correlation between cancer incidence and phytoestrogen consumption is found in breast cancer.…”
Section: Cancer and Phytoestrogensmentioning
confidence: 98%
“…Increased serum phytoestrogen concentrations have also been shown to be inversely correlated to risk of gastric cancer in a study of male and female Korean individuals [78]. Furthermore, Chinese ERα positive gastric cancer patients, had a significantly worse prognosis compared to those that were ERβ positive [79]. The most well characterized correlation between cancer incidence and phytoestrogen consumption is found in breast cancer.…”
Section: Cancer and Phytoestrogensmentioning
confidence: 98%
“…Non-genomic estrogen signaling mediated by ER-α was involved in the c-Src signaling pathway in SGC7901 GC cells (66). A recent study found that ERα expression in gastric cancer cells was increased by low concentrations of 17β-estradiol, which in turn resulted in increased proliferation by activating mitogen-activated protein kinase signaling pathway (67). In addition, knock down of ERα did not affect the proliferation, migration and invasion of gastric cancer cells (67).…”
Section: Gastric Cancer (Gc)mentioning
confidence: 98%
“…A recent study found that ERα expression in gastric cancer cells was increased by low concentrations of 17β-estradiol, which in turn resulted in increased proliferation by activating mitogen-activated protein kinase signaling pathway (67). In addition, knock down of ERα did not affect the proliferation, migration and invasion of gastric cancer cells (67). Compared with expression of ERα, expression of ERβ in noncancerous tissues was significantly higher in female rats compared with male rats (68).…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…Thus, the observed up-regulation of UBE2M and UBA3 in esophageal squamous cell carcinomas and intrahepatic cholangiocarcinoma could be repeated in gastric cancer as another organ of the digestive system. On the other hand, recently researchers proved the estrogen receptors (ERα, ERβ) involvement in the progression of gastric cancer by affecting P21, P27, P53, and E-Cadherin expressions (Tang et al 2017). Furthermore, several studies reported a decrease in the expression of these receptors related to poor prognosis of gastric cancer (Tang et al 2017).…”
Section: Predicted Driver Genes Of Hereditary Gastric Cancermentioning
confidence: 99%
“…On the other hand, recently researchers proved the estrogen receptors (ERα, ERβ) involvement in the progression of gastric cancer by affecting P21, P27, P53, and E-Cadherin expressions (Tang et al 2017). Furthermore, several studies reported a decrease in the expression of these receptors related to poor prognosis of gastric cancer (Tang et al 2017). UBE2M and UBA3 are factors that their overexpression downregulate the estrogen receptors expression (Fan et al 2003).…”
Section: Predicted Driver Genes Of Hereditary Gastric Cancermentioning
confidence: 99%